Analysis and monitoring of odour and semi-volatile organic compounds in different environmental matrices via gas chromatography-mass spectrometry - Urbancok, Dejan (2018)
Gas Chromatography Mass Spectrometry (GC-MS) combined with Thermal Desorption (TD) and solid phase extraction (SPE) methodologies were developed for the quantification and qualification of: •Polycyclic aromatic hydrocarbons (PAHs) and polychlorinated byphenyls (PCBs) bound on airborne particulate matter (PM) (different sizes of 10 and 2.5 μm). •The PAHs and organochlorine pesticides (OCPs) in various water samples collected in lower Himalayas in Bhutan. •The volatile organic sulfur compounds (VOSCs) in air. At a Nanyang Technological University (NTU) rooftop sampling site, airborne particulates were sampled in two different sizes of 10 and 2.5 μm between May 2015 to May 2016 and April 2016 to September 2016 for analysis of PM10 bound PAHs and PM2.5 bound PCBs, respectively. The same sampling site was used for collecting air samples for the analysis of odour VOSCs. One of the findings of this project is that when comparing PAHs abundances in Singapore to the other countries in the SEA and Asia in global Singapore has some of the lowest values of airborne PAHs, likely due to strict emission regulations for both traffic and industry sectors. In spite of this observation, the main problem for Singapore is trans-boundary pollution when the PM10 concentrations increased from a typical average reading of approximately 25 μg/m3 up to a concentration reaching over 300 μg/m3 during the high haze events, while PAH concentrations approximately doubled. In terms of the PCBs monitored when comparing data to the literature review reports on airborne PCBs in the region results showed there were not significant changes in the last 15 years. PCA analysis of factor loadings for every component extracted and compared to the work previously conducted in neighbouring countries suggested possible contribution of the emissions from electronic waste (incineration plant in Tuas) [62] and ship-dismantling activities [146]. Furthermore, SPE-GC-MS analysis of OCPs and PAHs were performed on water samples from 9 spring water sources, 7 storage facilities, 11 end user taps and water samples collected from the Lake “Teyminus” together with a glacier inlet sample collected in close proximity. This sampling campaign was conducted in and around Yonphula, Kanglung and Rongthung areas located in Lower Himalayas in Trashigang District of Eastern Bhutan. One of the major outcomes of this project is that out of 23 OCPs monitored, 8 were detected in concentrations within allowed admissible concentration for pesticides of 0.1 µg L-1. Comparing to the OCPs quantified, PAHs detected in lake samples including glacier and an inlet stream showed higher concentrations. All 16 targeted PAHs were detected and quantified in every sample. The most abundant PAHs were NAPH and ACP representing lighter PAHs and BbF, BkF, BaP, IcP, DhA and BghiP for the heavier PAHs. Dominance of this specific congeners suggested domestic heating and long distance transport from countries such as India, Nepal and China as a sources of the PAHs in this sampling site. At the end detailed study on volatile organic sulfur compounds including: dimethyl sulfide, carbon disulfide, propyl mercaptan, dimethyl trisulfide and 1-buthanethiol was performed to help to fill some data gap in the understanding of air quality in Singapore semi-urban atmosphere in terms of odour compounds since there hasn’t been any work done related tot his topic in Singapore.The occurrence of the VOSCs in semi urban ambient air was examined in terms of diurnal, inter-day and intra-day variations. Throughout all the sampling campaign, BuSH and PrSH were not detected in any samples. However, other 4 compounds (EtSH, DMS, DMTS and CS2) were detected with 100% detection frequency. All results were in a ppbv range and above instrumental and method detection limits. Overall, 4 months of statistical data calculated for all target VOSCs revealed that DMS and CS2 were the most dominant organosulfur compounds in the atmosphere.